2017
DOI: 10.1002/jcc.25094
|View full text |Cite
|
Sign up to set email alerts
|

Confinement induced thermodynamic and kinetic facilitation of some Diels–Alder reactions inside a CB[7] cavitand

Abstract: The effect of geometrical confinement on the Diels-Alder reactions between some model dienes viz. furan, thiophene, cyclopentadiene, benzene, and a classic dienophile, ethylene has been explored by performing density functional theory-based calculations. The effect of confinement has been imposed by a rigid macrocyclic molecule cucurbit[7]uril (CB[7]). Results indicate that all the reactions become thermodynamically more favorable at 298.15 K temperature and one atmospheric pressure inside CB[7] as compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 59 publications
(62 reference statements)
0
30
0
Order By: Relevance
“…Later on, they used a variety of theoretical methodologies to show that confinement has a significant effect on many classical chemical reactions. For example, they used a relative big molecular host to confine some model Diels‐Alder reactions and find the catalytic changes due to the confinement . The theoretical models they used range from numerical Hartree‐Fock (HF) to more sophisticated quantum‐fluid‐dynamics time‐dependent density functional methods developed by his group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later on, they used a variety of theoretical methodologies to show that confinement has a significant effect on many classical chemical reactions. For example, they used a relative big molecular host to confine some model Diels‐Alder reactions and find the catalytic changes due to the confinement . The theoretical models they used range from numerical Hartree‐Fock (HF) to more sophisticated quantum‐fluid‐dynamics time‐dependent density functional methods developed by his group.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they used a relative big molecular host to confine some model Diels-Alder reactions and find the catalytic changes due to the confinement. [25][26][27] The theoretical models they used range from numerical Hartree-Fock (HF) to more sophisticated quantum-fluid-dynamics time-dependent density functional methods developed by his group. Very recently, they wrote a feature article summarizing their results.…”
mentioning
confidence: 99%
“…We have previously found that binding in CB favors the closed conformation of the reactants, in agreement with experimental NMR measurements. The confinement of the reacting molecules have also been taken into account by computations (Chakraborty and Chattaraj, 2018 ). However, these binding effects amounting to 1–2 kcal/mol, only partially explain the catalytic effects of 4–5 kcal/mol, which have so far been unresolved.…”
Section: Introductionmentioning
confidence: 99%
“…Computational chemistry could be helpful in this concern, but relatively few computational studies have been published on the operating mode of supramolecular catalysts, [8,9,[17][18][19][20] although things may have changed in the last two years. [21][22][23][24] The systems are intrinsically challenging for computational chemistry: a large number of conformers, complicated reaction networks, and need for a sufficiently accurate description of weak interactions.…”
Section: Introductionmentioning
confidence: 99%